Culture values and entrepreneurial innovativeness: A comparative study of Malaysian ethnic entrepreneurs - Tehseen, Shehnaz *; Deng, P.; Wu, B.; Gao, Y. (Taylor & Francis, 2021)
Countries are often characterized with a diverse set of subcultures, exerting different impacts on innovation among different ethnic groups. This article comparatively analyzes how national culture, as measured by Hofstede's six cultural values, influences the entrepreneurial innovativeness (EI) of three Malaysian ethnic firms (Malaysian Chinese, Indian, and Malays). Based on a systematic investigation of survey data of 450 small to medium-sized firms (SMEs), we find positive influences of indulgence, collectivism, and low power distance on EI among the three ethnic entrepreneurs in Malaysia. Our study also finds that three other cultural values have a differential impact on Malaysia’s ethnic groups. While long-term orientation exerts a significant impact on Malaysian Chinese, masculinity and low uncertainty avoidance have significant but (surprisingly) opposite impacts on the three ethnic entrepreneurs. These similar and different impacts of cultural values on EI among different ethnic groups generates significant theoretical and practical implications.